RECOGNITION FOR SUSTAINABLE WATER SUPPLY PROJECT - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUALA LUMPUR, 9 December 2016 The project carried out by the Universiti Sains Malaysia team (USM) from the School of Civil Engineering (PPKA) together with the Selama Land and District Office in Perak received recognition by winning the National Blue Ocean Strategy (NBOS) Competition, under the Civil Service category today and took home the prize money of RM30,000.